Evaluation of the slow-release polylactic acid/polyhydroxyalkanoates active film containing oregano essential oil on the quality and flavor of chilled pufferfish (Takifugu obscurus) fillets. (15th August 2022) - Zheng, Hui; Tang, Haibing; Yang, Chunxiang; Chen, Jingwen; Wang, Li; Dong, Qingfeng; Shi, Wenzheng; Li, Li; Liu, Yuan
Highlights: Biodegradable PLA/PHA composite active packaging was successfully prepared. Simulated liquid release was combined with the actual release of pufferfish fillets. The effect of oregano essential oil on the flavor of pufferfish was investigated. Abstract: Active packaging is an innovative and effective way to extend the shelf life of food, but few studies have focused on the effect of its active ingredients on food flavor. This study aimed to develop slow-release polylactic acid/polyhydroxyalkanoates (PLA/PHA) active packaging containing oregano essential oil (OEO) and investigate the effect of active composite packaging on the flavor and quality of pufferfish fillets. The plasticizing effect of OEO increased the elongation at break (EAB) of the films from 23.36% to 65.80%. The adsorption of montmorillonite (MMT) reduces the loss of OEO during processing. The amount of active substance (carvacrol) released from PLA/PHA/OEO/MMT film to pufferfish was 9.70 mg/kg. The pufferfish fillets packed in PLA/PHA/OEO/MMT film showed the slightest difference on the 8th day from the beginning of storage. The slow-release composite films could extend the shelf life of pufferfish fillets by 2–3 days at 4 °C ± 1 °C.